STUDI PERBANDINGAN PERILAKU STRUKTUR GEDUNG DENGAN KOLOM BETON BERTULANG, KOLOM BAJA, DAN KOLOM KOMPOSIT - I Ketut Diartama Kubon Tubuh (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
A comparative study of the behavior of building structures with reinforced concrete columns, steel columns and composite columns was carried out by making six structural models. One reinforced concrete structure model (MC), one steel structure model (MS), two steel structure models with encased composite columns with circular (MEC-C) and square sections (MEC-S), and two models with structure steel with filled composite column with circular (MFC-C) and square (MFC-S) sections. Placement of the structure of the MC model is considered to be pinched to the ground, while other models are considered as joints. The dimensions of the IV-V floor column are made smaller than the dimensions of the columns below. Placement of the structure of the MC model is considered to be wedged in the ground, while placement of the model structure with steel or composite columns is considered as a joint. Structural behavior was observed from the results of elastic analysis in the form of deviations which then resulted in deviations between floors and drift ratio. The analysis shows, with a maximum P-M ratio range from columns of 0.79 to 0.88, all steel structure models do not meet the deviation requirements between permit floors on floors I and II. The orientation of all columns in the MS model was originally made in the same direction resulting in an imbalance of stiffness between the X and Y directions, overcome by changing the orientation of half of the total number of columns (hereinafter referred to as the MS-R model) also does not meet the deviation provisions between permit floors. The MC model, which is a reinforced concrete structure model, is the only model that meets the deviation rules between the floors. Apart from the rigid nature of the concrete material, it is also because the MC model uses the fixation fixation of the pins.